Does the Family Affluence Scale reflect parental earned income, education and occupational status?. (20th October 2021) - Corell, M; Chen, Y; Friberg, P; Petzold, M; Löfstedt, P
Abstract: Background: The Family Affluence Scale (FAS) is an alternative measure of families' socioeconomic conditions, developed for surveys to children and adolescents. It was adopted by the Health Behaviour in School-aged Children (HBSC) survey in 1993/94 and is frequently used in international research examining socioeconomic inequalities in health among children and adolescents. It has been validated in several countries, but not with register data. The aim of this study was to examine the external validity of the FAS among adolescents in Sweden, by using register data for parental earned income, level of education and occupational status. Methods: Data from the baseline (2015 − 2019) of the Study of Adolescence Resilience and Stress (STARS), comprising 2 283 13-year-olds in the region of Västra Götaland, were used. The FAS III consists of six items; unshared bedroom, car ownership, computer/tablet ownership, dishwasher, number of bathrooms and number of holidays abroad. Register data from Statistics Sweden (2014 − 2018) were linked to the adolescents. Pearson's and Spearman's correlation coefficients were calculated. Results: Total parental earned income was moderately correlated to adolescents' scoring on FAS (0.31 < r < 0.48, p < 0.01), depending on examination year. Correlations between mothers' and fathers' educational level and adolescent's scoring on FAS were low (r = 0.19 and r = 0.21 respectively, p < 0.01). FAS was higher among adolescents with working parents, but the correlation between parent's occupational status and FAS was low (r = 0.22, p < 0.01). The low FAS group mainly comprised low income households and the high FAS group mainly high income households. However, in the medium FAS group, all income quintiles were equally represented. Consequently, the medium FAS group should be used as the reference group. Conclusions: The FAS was moderately associated to total parental earned income and mainly identified low income and high income households. Key messages: The FAS may be used as an alternative measure of total parental earned income in studies based on self-reported socioeconomic status among adolescents. Ensuring that instruments intended to measure socioeconomic conditions are valid is crucial in public health.